An Integrative “Omics” Approach, for Identification of Bona Fides PLK1 Associated Biomarker in Esophageal Adenocarcinoma - Bibi, Nousheen; Rashid, Sajid; Nicholson, Judith; Malloy, Mark; O'Neill, Rob; Blake, David; Hupp, Ted (Current Cancer Drug Targets, 2019)
Background: The rapid expansion of genome-wide profiling techniques offers the opportunity to utilize various types of information collected in the study of human health and disease. Overexpression of Polo like kinase 1 (PLK1) is associated with esophageal adenocarcinoma (OAC), however biological functions and molecular targets of PLK1 in OAC are still unknown. Objectives: Here we performed integrative analysis of two “omics” data sources to reveal high-level interactions of PLK1 associated with OAC. Methods: Initially, quantitative gene expression (RPKM) was measured from transcriptomics data set of four OAC patients. In parallel, alteration in phosphorylation levels was evaluated in the proteomics data set (mass spectrometry) in OAC cell line (PLK1 inhibited). Next, two “omics” data sets were integrated and through comprehensive analysis possible true PLK1 targets that may serve as OAC biomarkers were assembled. Results: Through experimental validation, small ubiquitin-related modifier 1 (SUMO1) and heat shock protein beta-1 (HSPB1) were identified as novel phosphorylation targets of PLK1. Consequently in vivo, in situ and in silico experiments clearly demonstrated the interaction of PLK1 with putative novel targets (SUMO1 and HSPB1). Conclusion: Identification of a PLK1 dependent biosignature in OAC with high confidence in two omics levels proven the robustness and efficacy of our integrative approach.
Keywords: Omics